Anti-Fibrotic Potential of Angiotensin (1-7) in Hemodynamically Overloaded Rat Heart - Sykora, Matus; Kratky, Vojtech; Kopkan, Libor; Tribulova, Narcisa; Szeiffova Bacova, Barbara (International journal of molecular sciences, 2023)
The extracellular matrix (ECM) is a highly dynamic structure controlling the proper functioning of heart muscle. ECM remodeling with enhanced collagen deposition due to hemodynamic overload impairs cardiomyocyte adhesion and electrical coupling that contributes to cardiac mechanical dysfunction and arrhythmias. We aimed to explore ECM and connexin-43 (Cx43) signaling pathways in hemodynamically overloaded rat heart as well as the possible implication of angiotensin (1-7) (Ang (1-7)) to prevent/attenuate adverse myocardial remodeling. Male 8-week-old, normotensive Hannover Spraque-Dawley rats (HSD), hypertensive (mRen-2)27 transgenic rats (TGR) and Ang (1-7) transgenic rats (TGR(A1-7)3292) underwent aortocaval fistula (ACF) to produce volume overload. Five weeks later, biometric and heart tissue analyses were performed. Cardiac hypertrophy in response to volume overload was significantly less pronounced in TGR(A1-7)3292 compared to HSD rats. Moreover, a marker of fibrosis hydroxyproline was increased in both ventricles of volume-overloaded TGR while it was reduced in the Ang (1-7) right heart ventricle. The protein level and activity of MMP-2 were reduced in both ventricles of volume-overloaded TGR/TGR(A1-7)3292 compared to HSD. SMAD2/3 protein levels were decreased in the right ventricle of TGR(A1-7)3292 compared to HSD/TGR in response to volume overload. In parallel, Cx43 and pCx43 implicated in electrical coupling were increased in TGR(A1-7)3292 versus HSD/TGR. It can be concluded that Ang (1-7) exhibits cardio-protective and anti-fibrotic potential in conditions of cardiac volume overload.
Keywords: Angiotensin II; potkani transgenní; Male; hypertenze; angiotensin II; srdeční selhání; fibróza; srdce; mužské pohlaví; Hypertension; Fibrosis; Rats, Transgenic; krysa rodu Rattus; Animals; Heart Failure; zvířata; Rats; konexin 43; Connexin 43; Heart